A atenção institucional as pessoas que usam drogas : tratamento ou punição? - Cazanova, Ricardo Flores (2017)
The main purpose of this thesis is to determine if after the increase of the legislation originating from the 1988 Constitution regarding the issue of alcohol and drug use, the treatments provided by the Institutions that have this purpose have undergone alterations or still have characteristics of punishment. The study, which originated the present thesis, was integrated into the umbrella research Policies and Practices of Coping with Drug Addiction in Rio Grande do Sul / Brazil. Such umbrella research was delineated and operationalized by the Research and Social Policies Research Center (NEDEPS-PUCRS) and collaborators, under the coordination of Dr. Leonia Capaverde Bulla, in 2010. In order to carry out this study, based on the critical dialectic method , A mixed research approach was used with quantitative data from the database and the degra- cations of the umbrella research and information made available on Federal, State and Municipal Government official sites and institutions that meet the researched demand. It is therefore a study that includes, in addition to the aforementioned database, drug and mental health legislation, plans and programs implemented by the three spheres of government and interviews. From the analysis of the data it is possible to point out that despite the current legislation it is still possible to identify methodologies of care for people with alcohol and drug addictions a punitive, repressive character.